MicroRNA‐372 enhances radiosensitivity while inhibiting cell invasion and metastasis in nasopharyngeal carcinoma through activating the PBK‐dependent p53 signaling pathway. (18th January 2019) - Wang, Zhe; Mao, Ji‐Wei; Liu, Guang‐Yan; Wang, Fu‐Guang; Ju, Zai‐Shuang; Zhou, Dong; Wang, Ruo‐Yu
Abstract: Nasopharyngeal carcinoma (NPC) is a common cancer found in the nasopharynx, which plagues countless NPC patients. MicroRNA‐372 (miR‐372) has been reported to be involved in various tumors. Here, we explored the important role of miR‐372 in radiosensitivity, invasion, and metastasis of NPC. Microarray analysis was conducted to search the NPC‐related differentially expressed genes (DEGs) and predict the miRs regulating PBK, which suggested that miR‐372 could influence the development of NPC via PBK and the p53 signaling pathway. Importantly, miR‐372 was observed to target PBK, thus down‐regulating its expression. Then, NPC 5‐8F and C666‐1 cells were selected, and treated with ionization radiation and alteration of miR‐372 and PBK expression to explore the functional role of miR‐372 in NPC. The expression of miR‐372, PBK, Bcl‐2, p53, and Bax as well as the extent of Akt phosphorylation were measured. In addition, cell colony formation, cell cycle, proliferation, apoptosis, migration, and invasion were detected. At last, tumor growth and the effect of miR‐372 on radiosensitivity of NPC were evaluated. Besides, over‐expressed miR‐372 down‐regulated Bcl‐2 and PBK expression and the extent of Akt phosphorylation while up‐regulated the expression of p53 and Bax. Additionally, miR‐372 over‐expression and radiotherapy inhibited cell clone formation, proliferation, tumor growth, migration, invasion, and cell cycle entry, but promoted cell apoptosis. However, the restoration of PBK in NPC cells expressing miR‐372 reversed the anti‐tumor effect of miR‐372 and activation of the p53 signaling pathway. In conclusion, the study shows that up‐regulated miR‐372 promotes radiosensitivity by activating the p53 signaling pathway via inhibition of PBK. Abstract : In conclusion, the study shows that up‐regulated miR‐372 promotes radiosensitivity by activating the p53 signaling pathway via inhibition of PBK.